2015
DOI: 10.1080/09581596.2015.1067671
|View full text |Cite
|
Sign up to set email alerts
|

Colonial legacy and the experience of First Nations women in cervical cancer screening: a Canadian multi-community study

Abstract: Regular Papanicolaou (Pap) screening has dramatically reduced cervical cancer incidence in Canada since the 1950s. However, Indigenous women's rates of cervical cancer remain disproportionately high, a factor which is not acknowledged in national media or in educational materials reporting Canada's new cervical cancer screening guidelines. Here, we present findings from a cervical cancer screening initiative in Northwestern Ontario. Based on participatory action research, we worked with 10 First Nations commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 23 publications
2
90
0
3
Order By: Relevance
“…We reasoned that empowering women to take their own samples may help overcome some of the structural and cultural barriers First Nations women face when attending cervical screening 13 —a re-affirmed notion and deemed to be culturally appropriate by our community informants during the qualitative phase of the ACCSS. 17 18 DNA integrity from self-samples was excellent—an important factor to emphasise when promoting this screening method as some women reported being anxious that they were not taking their self-sample correctly. Greater than 95% of the samples could be HPV-tested and typed, confirming our earlier pilot data.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that empowering women to take their own samples may help overcome some of the structural and cultural barriers First Nations women face when attending cervical screening 13 —a re-affirmed notion and deemed to be culturally appropriate by our community informants during the qualitative phase of the ACCSS. 17 18 DNA integrity from self-samples was excellent—an important factor to emphasise when promoting this screening method as some women reported being anxious that they were not taking their self-sample correctly. Greater than 95% of the samples could be HPV-tested and typed, confirming our earlier pilot data.…”
Section: Discussionmentioning
confidence: 99%
“…In total, we retained 32 studies, four used qualitative (23)(24)(25)(26) and 28 used quantitative methodology (2,(16)(17)(18)(19)(20) . Included studies covered HCPs opinions from five continents: Europe (i.e., UK (47) , Germany (38) and Italy (39) ), North America (i.e., Canada (24,26,35) and the US (2, 16-20, 23, 29-31, 34, 36, 40-44, 46) ), Africa (i.e., Cameroon (28) and Nigeria (25) ), Asia (i.e., China (27) , Jordan (45) ,South Korea (33) and Thailand (37) ) and Oceania (i.e., Australia (32) ). Details of each included study can be found in Appendix A.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a slightly lower sensitivity and specificity in detecting cervical intraepithelial neoplasia (CIN2 and CIN3) of HPV testing on self-samples than of HPV testing on a clinician-taken sample (54,55) , Nelson et al (2017) found that 97% of women found selfsampling to be generally acceptable, 65% would prefer self-sampling over clinician-based sampling for HPV testing and considered self-sampling less embarrassing, respecting privacy and easy to use (56) . In our review, we found that HCPs viewed self-sampling as a facilitator of HPV testing as it alleviates women's concerns about privacy and body discomfort during Pap examination, has the potential to reach women in underserved locations and reduces the burden of women's return to the medical system (23,24) . Strategies to increase HCPs recommendations for self-sampling should take into consideration HCPs worries that self-sampling could be associated with missed opportunities to address other health issues and that women's decreased health literacy represents a barrier to an efficient screening, mostly due to poor quality of the self-collected sample (23,31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are notable difficulties in accessing Papanicolaou screening services among Status First Nations women living on reserve, including poor access to family phys icians, delivery of health care services on reserve by registered nurses who are not trained to provide Papanicolaou screening, and lack of culturally safe, trauma-informed cervical cancer screening services. [33][34][35] These challenges may contribute to lower rates of diagnosis of cervical cancer among Status First Nations women living on reserve.…”
Section: Open Researchmentioning
confidence: 99%